The Influence of Family, School and Peer Groups on Student’s Consumption Behavior Through Student Engagement of Senior High Schools in Pemalang Regency - Ujianingrum, Hening; Yanto, Heri; Murwatiningsih, Murwatiningsih (Journal of Economic Education, 2019)
Consumer behavior in general is a study of how someone decides to buy or consume a product. The influence of peer groups towards student’s consumption behavior can be seen through their daily lives. Among them are by having the same brand of goods such as cellphones, shoes, watches, accessories; watching the same movies that they consider to be good; idolizing the same actors and actresses; and consuming the same foods and drinks. Those behaviour indicate the influence of peer groups on student’s consumption behavior. It becomes problematic because the consumption behavior done by most of these students often cause economic problems for their families, their first environment before entering school. This phenomenon of student’s consumption behavior becomes more interesting considering into what extent economics knowledge they get in school being implemented in their daily decision makings. Factors influencing the consumption behavior of high school students in Pemalang Regency were suspected to be family, school and peer groups. The method of analysis used in this study was path analysis using Amoss software. The calculation results showed that students’ engagement had a significant influence on student’s consumption behavior with a CR value of 2.647, peer groups had a significant influence on student’s consumption behavior with a CR value of 5.446, family environment had no significant influence on student’s consumption behavior with a CR value of 1.322 (smaller than 1.96), the school environment had a significant influence on student’s consumption behavior with a CR value of 3.276. This study used data from Dapodik Academic Year 2018/2019 of Social Science students of Public Senior High Schools in Pemalang Regency.